Faktor-Faktor Yang Mempengaruhi Pembiayaan Bank Syariah di Indonesia - Nursantri Yanti (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This financing is in the form of funds from surplus units to deficit units with the aim of obtaining profit margins, rental income and income from proceeds. The bank's business activity in the form of financing with the principle of profit sharing is a form of economic equity in accordance with sharia guidelines, because its activities are proven to support asset turnover and flow productively. But in reality, Islamic banks are more dominant in channeling consumptive funds through buying and selling-based financing. This study analyzes and tests whether SBIS, CAR, FDR, NPF, and yields that can affect financing. The sample used in this study found 48 data sourced from data from Islamic Commercial Banks and Sharia Business Units for the 2017-2020 period. After processing the data using multiple linear regression, the results showed that SBIS, CAR, FDR, NPF, and Yield could affect financing significantly and by doing partial or simultaneous testing